2020
DOI: 10.13057/biodiv/d210818
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Molecular barcode and morphology analysis of Malva pseudolavatera Webb & Berthel and Malva sylvestris L. from Ecuador

Abstract: Abstract. Sarmiento-Tomalá G, Santos-Ordóñez E, Miranda-Martínez M, Pacheco-Coello R, Scull-Lizama R, Gutiérrez-Gaitén Y, Delgado-Hernández R. 2020. Short Communication: Molecular barcode and morphology analysis of Malva pseudolavatera Webb & Berthel and Malva sylvestris L from Ecuador. Biodiversitas 21: 3554-3560. In Ecuador, several plant species are used in traditional medicine without a criterion of family, genera, or chemical composition. The species of the genus Malva (Malva pseudolavatera Webb &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…The clade for D. adscendens CS had a 99% support while the D. molliculum CS clade was supported by only 61%, one of the lowest percentages obtained in this research. Despite the fact that the ITS2 marker has been reported to be successful in identifying specimens to the species level by up to 92.7% (24) and other studies on medicinal plants highly recommend the use of the ITS markers for species identi cation and differentiation (23,(25)(26)(27)(28), we found that is not the best marker for D. molliculum identi cation.…”
Section: Discussioncontrasting
confidence: 59%
“…The clade for D. adscendens CS had a 99% support while the D. molliculum CS clade was supported by only 61%, one of the lowest percentages obtained in this research. Despite the fact that the ITS2 marker has been reported to be successful in identifying specimens to the species level by up to 92.7% (24) and other studies on medicinal plants highly recommend the use of the ITS markers for species identi cation and differentiation (23,(25)(26)(27)(28), we found that is not the best marker for D. molliculum identi cation.…”
Section: Discussioncontrasting
confidence: 59%
“…Qualitative and quantitative differences were observed between both samples. These differences were associated to intrinsic factors, mainly to the genetical variability inter-species, previously reported (Sarmiento et al, 2020a).…”
Section: Phytochemical Compositionmentioning
confidence: 66%
“…The ITS2 revealed a low percentage of identification (80.49%) with BLASTn, suggesting that species differentiation could be detected using the ITS2. The results from other studies have indicated a better resolution for species identification using the ITS2 in medicinal plants (Techen et al, 2014;Zhang et al, 2016;Bustamante et al, 2019;Sarmiento-Tomalá et al, 2020).…”
Section: Molecular Barcode Sequencesmentioning
confidence: 96%